Assessment of Indoor Air Quality in Renovated Buildings of Liepāja Municipality. (June 2016) - Asere, Līva; Mols, Toms; Blumberga, Andra
Abstract: The research of five educational institution buildings and three municipality department buildings were carried out in Liepāja municipality, Latvia. Aim of the study is to draw attention to finding balance among energy efficiency, thermal comfort and indoor air quality dilemma. The research of recently renovated public sector buildings was done. The combination of factors that form microclimate and indoor air quality are described in the paper. Emphasis is put on a person's ability to perform mental tasks in regards of changes in thermal comfort and air quality. Surveys of buildings' inhabitants and economic aspects of human productivity changes were carried out in the research. Also four ventilation scenarios have been modelled and economic benefits of each scenario have been assessed. Different air exchange rates can make 19% human productivity improvement. Using ventilation systems as it is designed already gives economic benefit and not all the buildings need additional investments for new system implementation. The economic benefit in four buildings is more than 20 000 euro already in second year. The priority for planning, designing and managing education institution buildings should be indoor environment and thermal comfort of inhabitant.